Determination of the Heave and Pitch Motions of a Floating Cylinder by Analytical Solution of its Diffraction Problem and Examination of the Effects of Geometric Parameters on its Dynamics in Regular Waves - Ghadimi, Parviz; Paselar Bandari, Hadi; Bankhshandeh Rostami, Ali (International Journal of Applied Mathematical Research, 2012)
In this paper, diffraction problem of a floating vertical circular cylinder is studied. Detailed analytical solution for the boundary value problem to evaluate the wave loads for the cylinder with heave and pitch motions in water of finite depth in the presence of an incident wave, has been presented. Accordingly, diffraction problem for a truncated vertical circular cylinder of radius  in water of finite depth  has been considered. Incident wave used in this problem, is assumed to be linear with amplitude . In order to calculate the added mass and damping coefficients of the pitch motion of the body, strip theory is applied. For the heave motion, the hydrodynamic coefficients are found by the submerged disk method. Parametric studies of the effects of the wave excitation force on the floating cylinder have been performed for two different cases: 1) constant draft of the cylinder with varying water depth and 2) varying draft of the cylinder with constant water depth.